Visual Basic.Net Based Library Information System - Pasaribu, Appril Cillia; Marbun, Nasib (Information Technology and Science (ITScience), 2024)
Libraries are important institutions in the world of education as a place to develop knowledge through various book references. In a library, there is generally a very large stock of books. In addition, the number of book loan and return transactions continues to increase over time. Library data processing that still uses conventional methods, namely with notebooks and pens often causes problems, such as the use of a lot of time, data redundancy, and data loss. This research aims to develop a library data management system from a conventional system to a computerized one. The system that the author offers in this study is a visual basic net-based library information system equipped with a MySQL database as the right data storage and Crystal Report as a medium for attaching to print data processing reports that have been done. The system development method used in this research is the Waterfall method. The results of this research are in the form of a library information system that can be used on computer devices with the windows operating system.